The Mucosal and Serological Immune Responses to the Novel Coronavirus (SARS-CoV-2) Vaccines - Chan, Renee W. Y.; Liu, Shaojun; Cheung, Jonathan Y.; Tsun, Joseph G. S.; Chan, Kate C.; Chan, Kathy Y. Y.; Fung, Genevieve P. G.; Li, Albert M.; Lam, Hugh Simon (Frontiers in Immunology, 2021)
Background: Although serological antibody responses induced by SARS-CoV-2 vaccines are well characterized, little is known about their ability to elicit mucosal immunity. Objectives: To examine and compare the mucosal and systemic responses of recipients of the two different vaccination platforms: mRNA (Comirnaty) and inactivated virus (CoronaVac). Methods: Serial blood and nasal epithelial lining fluid (NELF) samples were collected from the recipients of either Comirnaty or CoronaVac. Plasma and NELF immunoglobulins A and G (IgA and IgG) specific to SARS-CoV-2 S1 protein (S1) and their neutralization effects were quantified. Results: Comirnaty induced nasal S1-specific immunoglobulin responses, which were evident as early as on 14±2 days after the first dose. In 64% of the subjects, the neutralizing effects of NELF persisted for at least 50 days. 85% Comirnaty recipients exhibited S1-specific IgA and IgG responses in plasma by 14±2 days after the first dose. By 7±2 days after booster, all plasma samples possessed S1-specific IgA and IgG responses and were neutralizing. The induction of S1-specific plasma antibodies by CoronaVac was IgG dominant, and 83% of the subjects possessed S1-specific IgG by 7±2 days after booster, with neutralizing effects. Conclusion: Comirnaty induces S1-specific IgA and IgG responses with neutralizing activity in the nasal mucosa, similar response is not seen with CoronaVac. Clinical implication: The presence of a nasal response with mRNA vaccine may provide additional protection compared with inactivated virus vaccine. However, whether such widespread immunological response may produce inadvertent adverse effects in other tissues warrants further investigation.